Outcomes following venetoclax‐based treatment in therapy‐related myeloid neoplasms. Issue 8 (27th May 2022) - Shah, Mithun Vinod; Chhetri, Rakchha; Dholakia, Ruchita; Kok, Chung H.; Gangat, Naseema; Alkhateeb, Hassan B.; Al‐Kali, Aref; Patnaik, Mrinal M.; Baranwal, Anmol; Greipp, Patricia T.; He, Rong; Begna, Kebede H.; et al.
Abstract: Therapy‐related myeloid neoplasms (t‐MN) are aggressive malignancies in need of effective therapies. The BCL‐2 inhibitor venetoclax represents a paradigm shift in the treatment of acute myeloid leukemia. However, the effectiveness of venetoclax has not been studied in a large cohort of t‐MN. We retrospectively analyzed 378 t‐MN patients, of which 96 (25.4%, 47 therapy‐related acute myeloid leukemia, 1 therapy‐related chronic myelomonocytic leukemia, 48 therapy‐related myelodysplastic syndrome) received venetoclax. Median interval from t‐MN to venetoclax initiation was 2.9 (Interquartile range [IQR] 0.7–12) months, and patients received a median of 3 (IQR 1–4) cycles. The composite complete remission (CRc) rate, median progression‐free survival (PFS), and overall survival (OS) were 39.1%, 4.9 months, and 7 months, respectively. The upfront use of venetoclax and achieving CRc were associated with improved survival, whereas the presence of Chromosome 7 abnormalities was associated with an inferior survival. Neither the TP53‐status nor the percent bone marrow blast predicted the likelihood of CRc or survival. Paired genetic analysis performed at venetoclax initiation and failure did not show the evidence of the selection of the TP53 ‐mutated clone. In a propensity‐matched analysis, the use of venetoclax‐based regimen as the first‐line therapy was associated with a superior survival compared to hypomethylating agent (HMA)‐based first‐line therapy (9.4 vs. 6.1 months, p  = .01). We conclude that the upfront use of venetoclax with HMA improved survival, though PFS and OS remain poor. As the phenotype at diagnosis or the percent blasts did not predict outcomes, venetoclax should be studied in all t‐MN phenotypes.